Frequency distribution of inflectional properties of nouns: data on written Italian - De Martino, Maria; Bracco, Giulia; Laudanna, Alessandro (CHIMERA: Revista de Corpus de Lenguas Romances y Estudios Lingüísticos, 2023)
The inflectional features of words show distributional peculiarities that affect the cognitive processing of language. For instance, it has been consistently reported that the association between the grammatical gender and other inflectional properties of nouns affects comprehension and production processes. However, reliable quantitative data about the distribution of nouns’ inflectional properties are scarce. The paper analyzes the inflectional system of nouns in Italian, a language where nouns are inflected for gender and number and are organized into different inflectional classes. The DeGNI lexical database (De Martino et al., 2019) was interrogated in order to obtain measures of the distribution of genders, gender suffixes and declensional patterns of the Italian nouns.